Rationalization in the ethanol-gas recognition mechanism of Al-doped ZnO nanoparticulate thin film defined on a highly integrated micro hot plate. (17th May 2019) - Galati, C; Spinella, N; Gervasi, L; Reina, S; Renna, L
Abstract: The gas sensor integration in smart devices, represents a huge step forward for health and environmental sensing applications. Several technical problems as well as the insufficient rationalization in the gas-recognition mechanisms still impede their development. Addressing this challenge, an ethyl alcohol/Al-doped ZnO interaction experiment is designed, exploiting a reliable chemiresistive thin film-based gas sensor. An ink-jet printing technique is chosen to deposit the nanostructured active layer on the highly integrated micro hot plate. Deposited sensing layer, is investigated with scanning electron microscopy, energy dispersive x-ray spectroscopy and atomic force microscopy. Conformal coating and profiled signals according to the covered sensor structure were achieved. The sensing results demonstrate a reproducible dynamic gas response with a rapid initial decrease in resistance, followed by a steady rise in conductivity at a different rate, until it plateaus. The well-defined signal profile, with the peculiar inflection points, has enabled an interpretation of the chemical reaction mechanism.